Effectiveness of three methods of dental age estimation in living adults, Huanuco region, Peru - Solís Adrianzén, Ronald Christian (2023)
Objective. To determine the effectiveness of three methods for estimating dental age in living adults in the Huanuco region. Methods. This was an applied research with a cross-sectional design, based on a correlational, comparative, quantitative approach. It was carried out on 50 teeth of living persons between 25 and 70 years of age in the region of Huánuco. The data collection techniques used were observation and measurement, using the data collection form as an instrument. The age of each tooth was estimated with the methods of "not effective" Lamendin, Prince and Ubelaker, Bang and Ramm, and when compared with the chronological age, the effectiveness of each method was established. The chi-square and ANOVA tests were used for the hypothetical contrast. Results. The methods of Prince and Ubelaker 86 % and Lamendin 94% were "effective" in estimating dental age, and no signifcant differences were found between them, unlike the method of Bang and Ramm, which was "not effective" in 92 %, there being significant differences with the methods of Prince and Ubelaker or Lamendin, in relation to effectiveness. Conclusion. The results of the study show that for the estimation of dental age in the population studied the Prince and Ubelaker and Lamendin methods are effective, while the Bang and Ramm method is not effective.